HOW UNIQUE IS SOUTH AFRICAN MILITARY INTEGRATION? - Licklider, Roy (Scientia Militaria - South African Journal of Military Studies, 2015)
The study of civil war since the end of the Cold War has uncovered several interesting, counter-intuitive facts. The first is that civil wars do end. Depending on how one counts, there have been 100–200 such wars since 1945.[i] There are now fewer than ten, and some of them are new rather than old. Of course, some of these may break out again (a gentleman on a flight to Atlanta once explained to the author that the American Civil War was not yet over), but it is not likely that most will, let alone all. Indeed, every major power has had one or more civil wars which have ended: the French, Russians and Chinese after their revolutions; Germany, after the wars of unification (or the Thirty Years War, if you want to go back that far); the British, after the War of the Roses and its Civil War. The United States has done it twice: after the American Revolution and after the American Civil War. But it is fair to say that we do not really understand how large numbers of people who have been killing one another with considerable skill and enthusiasm are somehow able to create working political communities.[i] Themne’r, L & Wallensteen, P. Armed Conflicts 1946-2013. Journal of Peace Research 51/4, 2014, 541.